2021
DOI: 10.3390/vaccines9101147
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to Vaccination against SARS-CoV-2 in Patients with Immune-Mediated Diseases

Abstract: Aberrant deployment of the immune response is a hallmark pathogenic feature of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-related disease (COVID-19), possibly accounting for high morbidity and mortality, especially in patients with comorbidities, including immune-mediated disorders. Immunisation with SARS-COV-2 vaccines successfully instructs the immune system to limit viral spread into tissues, mitigate COVID-19 manifestations and prevent its most detrimental inflammatory complications in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 90 publications
0
8
0
Order By: Relevance
“…It should be added that in times of broad vaccination against COVID-19 in Western countries, one study demonstrated that the overall response rate to COVID-19 vaccine in patients suffering from systemic rheumatic diseases treated with JAKi remained high, 109 in line with rates reported with other immunosuppressants. 110 …”
Section: Introductionmentioning
confidence: 99%
“…It should be added that in times of broad vaccination against COVID-19 in Western countries, one study demonstrated that the overall response rate to COVID-19 vaccine in patients suffering from systemic rheumatic diseases treated with JAKi remained high, 109 in line with rates reported with other immunosuppressants. 110 …”
Section: Introductionmentioning
confidence: 99%
“… 22 Consistent immunogenicity and safety findings were reported in two meta-analyses, however, studies focusing primarily on SLE patients were scarce and data of in-activated vaccines was very limited. 23 , 24 In a recent phase 4 trial conducted in Brazil comparing 910 adults with ARD (25.5% with SLE, 38.2% on glucocorticoids, 13.1% on myophenolate) and 182 matched healthy controls, both the rates of anti-SAR-CoV-2 IgG seroconversion (70.4% vs 95.5%, p < 0.001) and neutralizing antibody positivity (56.3% vs 79.3%, p < 0.001) were significantly lower in the ARD group 6 weeks after the second dose of CoronaVac. 15 The short-term immunogenicity overall was regarded acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…These observations are in line with previous studies, both considering patients with SLE and other RDs. Most studies reported a rate of flare ranging from 3% to 12%, with a preponderance of musculoskeletal and constitutional involvement [ 21 , 22 , 23 , 24 ]. Interestingly, patients, who experienced an adverse reaction, also had a higher disease flare rate.…”
Section: Discussionmentioning
confidence: 99%